Quantitative Prediction of Natural Fractures in Shale Oil Reservoirs - Lei Gong; Shuai Gao; Bo Liu; Jianguo Yang; Xiaofei Fu; Fei Xiao; Xiaocen Su; Rongzhi Fu; Qi Lu (Geofluids)
Natural fractures are the key factors controlling the enrichment of shale oil. It is of great significance to clarify the distribution of natural fractures to guide the selection of sweet spots for shale oil. Taking the Qing-1 Member shale oil reservoir in the northern Songliao Basin, China as an example, a new method considering the factors affecting fracture distribution was proposed to quantitatively predict the structural fractures. And the effect of natural fractures on shale oil enrichment was discussed. Firstly, the types and characteristics of fractures in shale oil reservoirs are characterized by using core and outcrop data. Combined with the experimental analysis, the influences of fault, mechanical stratigraphy, mineral composition and content, TOC, and overpressure on fracture intensity were clarified. Then, the number and density of fractures are quantitatively predicted according to the power-law distribution of fault length. Next, geomechanical simulation and fracture prediction were carried out on the model which was established with comprehensive consideration of the influencing factors of fracture distribution. Finally, the fracture distribution is evaluated comprehensively based on above prediction. The prediction results in this work are consistent with the core measurements.